Bio‐Acrylates Production: Recent Catalytic Advances and Perspectives of the Use of Lactic Acid and Their Derivates. Issue 1 (19th December 2018) - Makshina, Ekaterina V.; Canadell, Judit; van Krieken, Jan; Peeters, Elise; Dusselier, Michiel; Sels, Bert F.
Abstract: The production of drop‐in chemicals from bio‐based renewable sources is gaining a lot of momentum due to proven negative impact of fossil‐based economy on environment and society. In this Review, various bio‐derived platform molecules are assessed as renewable alternatives to fossil resources for the catalytic production of acrylates. Acrylic acid and its esters are key building blocks of a large number of high‐value oligomers and polymers in the current industry. In spite of the encouraging successes reported on gram or lab‐scale, real implementation of bio‐based examples remain scarce mainly due to the current high cost and limited availability of the bio‐based substrates. As lactic acid and their derivatives are one of the most promising feedstocks for bio‐acrylate production, they are the main focus of this Review. Abstract : The key to the feedstock : Acrylic acid and esters are key monomers for large number of high‐value polymers. Various platform molecules originated from different biomass feedstock were assessed as potential substituents of current propylene‐based industrial production. This Review focuses on the use of lactic acid and their derivatives as the promising feedstock for bio‐based acrylates production.